Motilitas dan viabilitas semen rusa timor (Cervus timorensis) menggunakan pengencer yang berbeda pada suhu 5oC - Achadiah Rahmawati (Faculty of Animal Science, Universitas Brawijaya, 2010)
The aim of the research was to reduce inbreeding of Timor deer (Cervus timorensis). This research used semen ejaculated from 8 hard Timor deers with aged 4-8 years old. Semen was collected by electroejaculator without aenesthation. Ejaculate semen was evaluated by both macroscopically and microscopically based on different diluters (andromed®and egg yolk skim) during freezing processes (fresh, before freezing and post thawing). The result indicated that fresh semen volume was 1.01+ 0.21ml, pH was 6.95+0.09 with white milk-creamy colour, had a medium-opaque consistency and typical odor. Microscopic observation showed that the mass motility was 2+-3+ and individual motility was 80.6+5.63%. Sperm concentration was 4728.75+2386.66 milion/ml with viability percentage was 89.16+6.06% and abnormal sperm were 10.37+2.31%. Individual motility and viability percentage before freezing using andromed® and egg yolk skim were 59.38+4.17% and 26.88+7.53% and 80.83+5.86% and 69.28+6.70% respectively. The research concluded that andromed® was effective to maintain motility and viability percentage before freezing. Based on this research, researcher suggests to use andromed® that effective to maintain freezing process quality for future research. Keyword: Rusa deer, before freezing, diluters